User-centric plug-and-play functionality for IPv6-enabled wireless sensor networks - Neves, P.A.C.S. (2011)
“Copyright © [2010] IEEE. Reprinted from 2010 IEEE International Conference on Communications. ISBN:978-1-4244-6402-9. This material is posted here with permission of the IEEE. Internal or personal use of this material is permitted. However, permission to reprint/republish this material for advertising or promotional purposes or for creating new collective works for resale or redistribution must be obtained from the IEEE by writing to pubs-permissions@ieee.org. By choosing to view this document, you agree to all provisions of the copyright laws protecting it.”